Rationale for using surrogate markers for adenomyosis lesions in animal models: A narrative review - Sri Adeyana; Muhammad Yusuf (Science Midwifery, 2025)
Adenomyosis is a gynecological disease characterized by the invasion of endometrial glands and stroma into the myometrium, often causing symptoms of dysmenorrhea, abnormal uterine bleeding, and infertility. Basic research using animal models is important for understanding the pathogenesis mechanism and evaluating new interventions, but clinical symptoms in humans are difficult to measure directly in experimental animals. Therefore, surrogate markers that can objectively represent the clinical condition are needed. Methods: This literature review was compiled following the PRISMA 2020 guidelines. Articles were searched in PubMed, Scopus, and Web of Science databases for publications from 2015â€“2025. Inclusion criteria included original research articles (controlled trials, cohort, or cross-sectional studies) written in English, focusing on the use of surrogate markers in animal models of adenomyosis. Review articles, editorials, and publications without DOI were excluded. Results: A total of six primary studies met the inclusion criteria, most of which used the Institute of Cancer Research (ICR) mouse model with neonatal tamoxifen induction. Surrogate markers used can be grouped into three categories: (1) histological markers, such as the depth of myometrial infiltration and the degree of fibrosis (Masson staining, collagen I/IV, Î±-SMA), (2) functional markers, such as uterine contractility and pain behavior tests (hotplate latency), and (3) molecular markers, such as TGF-Î²1/p-Smad3, COX-2, TRPV1, NGF, PR-B, OTR, vimentin, and E-cadherin. In addition, several studies have assessed reproductive markers (LIF expression and implantation rate) as fertility surrogates. The results of these studies show a consistent relationship between adenomyosis progression and fibrosis, molecular dysregulation, hyperalgesia, and changes in uterine contractility. Interventions such as resveratrol, anti-platelet, and TGF-Î²1 neutralizing antibodies have been shown to improve these markers. Surrogate markers in animal models of adenomyosis have proven rational and useful for assessing disease progression and the effects of interventions. Although translational validity to humans is still limited, histological, functional, molecular, and reproductive markers can be an important bridge between basic research and clinical application in adenomyosis.